People’s Purchase Intention Toward Electric Cars - M Yosi Ramadan; M Rafi Mudzakky; Ahmad Nuh (Penerbit Hellow Pustaka, 2024)
The aim of this research is to determine the influence of the variables trust, environmental knowledge, gender, perceived behavioral control, and subjective norms on the intention to purchase electric vehicles. This study shows that trust has a significant positive influence on purchase intentions, and people who have high trust in electric vehicle brands are more likely to buy electric vehicles. Environmental knowledge also has a positive impact on purchase intentions, because people who have high environmental knowledge are more likely to buy environmentally friendly electric vehicles. Gender does not have a significant effect on purchase intention, but perceived behavioral control and subjective norms have a significant positive effect on purchase intention. The findings of this research indicate that marketing strategies that consider trust, environmental knowledge, and subjective norms can increase electric vehicle purchase intentions. This research will contribute to the development of more effective marketing strategies for electric vehicle brands.